Factors of (dis)satisfaction with body self-image in adolescence - Guilherme, José Francisco Nunes; Martins, Carla Alexandra Ramalho de Sena; Nunes, Maria Cristina de Oliveira Salgados; de Jesus, Saúl Neves (Seven Editora, 2024)
In adolescence, young people have to adapt to almost radical transformations, being the (dis)satisfaction with body self-image a reality. The aim of this research is to determine the relationship between physical condition and (dis)satisfaction with body self-image. To know how (in)satisfaction with body self-image relates to male versus female and analyse the association with academic achievement at a global level, according to gender and age. Participated 1517 adolescents, 701 males (46.18%), aged between 12 and 17 years. The physical condition was assessed by Fitnessgram, the (dis)satisfaction with body self-image, using the Collins Silhouette Scale (1991), was adapted by Simões (2014), and the academic performance by the arithmetic average of the curriculum subjects. There was a statistically significant relationship between (dis) satisfaction with body self-image and physical fitness level groups in the global sample and in males. The associations between body image (dis)satisfaction and academic achievement, global, male, and female gender, are not significant (p < 0.05). Between age and (in)satisfaction with body self-image globally and in women, the correlations are negative, significant, and weak. DOI:https://doi.org/10.56238/sevened2024.015-017